1984
DOI: 10.1148/radiology.152.2.6739817
|View full text |Cite
|
Sign up to set email alerts
|

Gated magnetic resonance imaging of the normal and diseased heart.

Abstract: Gated cardiac magnetic resonance (MR) images were obtained in two normal volunteers and 21 adults with a variety of cardiovascular abnormalities. The images were correlated with data from clinical examinations, electrocardiograms, and cardiac catheterization. Gated cardiac images were superior to nongated images. Combined cardiac and respiratory gated images were superior to images obtained with cardiac gating only, but acquisition time was longer. Portions of the coronary arteries were visualized in seven of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

1985
1985
2011
2011

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…Early attempts at coronary MRA with conventional spin-echo MR were met with limited success. In 1984, Lieberman et al 170 were able to visualize portions of the coronaries in only 7 of 23 patients, whereas Paulin and colleagues 23 identified the origin of the left main coronary artery in all 6 subjects examined and the RCA ostium in 4 of the 6 individuals. No coronary stenoses were identified in either report.…”
Section: Mra Of the Coronary And Pulmonary Arteriesmentioning
confidence: 99%
“…Early attempts at coronary MRA with conventional spin-echo MR were met with limited success. In 1984, Lieberman et al 170 were able to visualize portions of the coronaries in only 7 of 23 patients, whereas Paulin and colleagues 23 identified the origin of the left main coronary artery in all 6 subjects examined and the RCA ostium in 4 of the 6 individuals. No coronary stenoses were identified in either report.…”
Section: Mra Of the Coronary And Pulmonary Arteriesmentioning
confidence: 99%
“…Previous studies have demonstrated the utility of cardiac gated NMR to image many cardiac malformations including septal defects, great vessel malpositions, coarctation of the aorta, cardiac tumors, and surgically created aorticopulmonary shunts [1][2][3] . In addition, the proximal coronary artery has been visualized by the NMR imaging technique [7] . The current study, to our knowledge, represents the first documentation of a CAVF by NMR imaging .…”
Section: Pediatric Cardiology Discussionmentioning
confidence: 99%
“…[66][67] The advantage of without contrast and radiation with MR makes it preferable for younger athletes and renal insufficient patients to identify possible coronary artery disease as well as MB. In addition, calcified lesions at MDCT images show positive diagnosis or cannot be clearly demonstrated for the artifact from calcification in many cases.…”
Section: Detection Of Mb With Magnetic Resonance Imaging (Mr)mentioning
confidence: 99%